The Role of Health Literacy Promotion in Decreasing Vaginal Infection: A Message to Health Policy Makers - Mostafa Peyvand; shiva kargar (Shahid Sadoughi University of Medical Sciences, 2021)
vaginal infection is one of the prevalent problems among the women especially at the age of pregnancy. It can cause death and other complications such as cervical cancer, abortion, premature birth, and infertility. Different infectious organisms can affect the female reproductive system, and almost 95 % of vaginal infections are caused by Candida albicans, Gardnerella vaginalis, and Trichomonas vaginalis microorganisms. Vaginal infections do not usually have any symptom; however, symptoms such as vaginal discharge, irritation, itching, and smelly vaginal discharge can indicate vaginal infection (1). In the health evaluation visit from Sibo Soran city in Sistan & Baluchestan province in East of Iran, qualitative interviews with health staff and the native women revealed that the prevalence of vaginal infections is increasing in this region; the interviewees mentioned the causes of this prevalence as inobservance of healthy behaviors and hygiene, urinary habits, sexual behaviors, eating habits, lack of diagnostic equipment's, limited access to healthy water, and the low level of health literacy in this city. Nowadays, health literacy is considered as a fundamental indicator affecting the results and the costs of healthcare services, and it is also a requisite for healthcare systems. Health literacy is widely considered as a health determinant and a prioritized issue in public health policies. Low health literacy is related to low health, extensive inequality, and higher costs of health system. Health literacy enables the individuals to play a more active role in changing their surrounding environment to affect health level (2).